Hong Kong portrait of a family - Meredith, Burgess; Nye, Barry (WQED/Pittsburg : National Geographic Society, 1989)
Depicts life in Hong Kong as seen through the eyes of a Chinese family of 13, whose daily lives center around their boat store in Kong Kong Habor.
Keywords: Tangka (Chinese people); Hongkong -- Social life and customs